Propuesta de desarrollo turístico para la parroquia Amaluza, cantón Espíndola. - Troya Salinas, Mery Elizabeth (2024)
Tourism development in local communities is crucial for tourism planning, obtaining benefits for both the community and the locality. The main objective of this curricular integration project was to propose a tourism development plan for the Amaluza parish, Espíndola canton. Additionally, two specific objectives were established: to diagnose the current tourism situation in the Amaluza parish, Espíndola canton, and to design tourism proposals that allow the tourism development of the Amaluza parish, Espíndola canton. For the research, bibliographic, deductive, analytical-synthetic, and descriptive methods were employed. To establish the strategies, an adapted methodological guide for the creation of cantonal tourism development plans (AME) was used, taking into account the phases that the territory permitted, thus obtaining relevant information about the parish. Firstly, a diagnosis was conducted, covering social, cultural, economic, environmental, political, and tourism aspects. The hierarchical classification of the parish's tourist attractions was also performed using the MINTUR 2018 records. To determine the potential demand, a survey technique was employed with the assistance of the PEA from the cantons of Loja, Catamayo, Gonzanamá, Quilanga, Calvas, and Espíndola. A mathematical SWOT analysis was conducted, and factors with the highest weight were considered to determine the strategies. These strategies were socialized and validated by the stakeholders involved in Amaluza parish's tourism activities. The results revealed that the parish has seven tourist attractions: five cultural manifestations and two natural attractions, all classified as tier II. Additionally, there is intangible heritage, archaeological assets, and buildings corresponding to residential houses. The strategies are related to tourism products, tourist signage, training, and the promotion and diffusion of services and activities offered by the parish.